2023
DOI: 10.3390/w15081535
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in 1,4-Dioxane Removal Technologies for Water and Wastewater Treatment

Abstract: 1,4-Dioxane is a contaminant of emerging concern and a probable human carcinogen that has been widely detected in aqueous environments. However, the removal of 1,4-dioxane by conventional water and wastewater treatment plants had proven to be ineffective due to its unique physicochemical properties. The development of innovative technologies for both in-situ and ex-situ treatment of 1,4-dioxane to meet increasingly strict standards is in urgent need. This review summarizes the current available physicochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…Toxicological studies have indicated that exposure to 1,4-D can cause health harms such as nasal cavity carcinomas and liver and gall bladder carcinomas [ 5 ]. Therefore, it has been classified as a Group 2B probable human carcinogen by the International Agency for Research on Cancer (IARC) [ 6 ]. Data show that approximately 21% of the drinking water supplies in the United States are contaminated with 1,4-D [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxicological studies have indicated that exposure to 1,4-D can cause health harms such as nasal cavity carcinomas and liver and gall bladder carcinomas [ 5 ]. Therefore, it has been classified as a Group 2B probable human carcinogen by the International Agency for Research on Cancer (IARC) [ 6 ]. Data show that approximately 21% of the drinking water supplies in the United States are contaminated with 1,4-D [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though 1,4-D is not federally regulated in the US, several states have established notification levels and guidelines. The acceptable concentrations of 1,4-D are low, typically in the range of (sub-) parts per billion (ppb), e.g., New York State set up a level of 1 µg L −1 , and several other states have established water criteria with the concentration ranging from 0.3 to 7.2 µg L −1 [ 6 ]. The prevalence, persistency, and toxicity of this emerging pollutant have prompted increasing attention, highlighting the necessity for cost-effective treatments to mitigate its exposure risk [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,4-dioxane (1,4-D) is an emerging organic pollutant with strong hydrophilicity and high stability in aqueous environments [1,2]. 1,4-D has been extensively detected in urban sewage systems, groundwater, and surface water worldwide [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…1,4-D may cause serious damage in humans and environmental problems and has been classified a suspected carcinogen and an endocrinedisrupting chemical by reputable organizations such as the Agency for Toxic Substances and Disease Registry and the International Agency for Research on Cancer [9,10]. The concentration of 1,4-D in drinking water is recommended to be below 50 µg/L by the World Health Organization [1]. Due to a low Henry's law constant (4.80 × 10 −6 atm m 3 /mol at 25 • C) and high solubility, 1,4-D is difficult to remove using coagulation and adsorption [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation